Poincaré Plot Area of Gamma-Band EEG as a Measure of Emergence From Inhalational General Anesthesia - Hayase, Kazuma; Kainuma, Atsushi; Akiyama, Koichi; Kinoshita, Mao; Shibasaki, Masayuki; Sawa, Teiji (Frontiers in Physiology, 2021)
The Poincaré plot obtained from electroencephalography (EEG) has been used to evaluate the depth of anesthesia. A standalone EEG Analyzer application was developed; raw EEG signals obtained from a bispectral index (BIS) monitor were analyzed using an online monitoring system. Correlations between Poincaré plot parameters and other measurements associated with anesthesia depth were evaluated during emergence from inhalational general anesthesia. Of the participants, 20 were adults anesthetized with sevoflurane (adult_SEV), 20 were adults anesthetized with desflurane (adult_DES), and 20 were pediatric patients anesthetized with sevoflurane (ped_SEV). EEG signals were preprocessed through six bandpass digital filters (f0: 0.5–47 Hz, f1: 0.5–8 Hz, f2: 8–13 Hz, f3: 13–20 Hz, f4: 20–30 Hz, f5: 30–47 Hz). The Poincaré plot-area ratio (PPAR=PPA_fx/PPA_f0, fx=f1~f5) was analyzed at five frequency ranges. Regardless of the inhalational anesthetic used, there were strong linear correlations between the logarithm of PPAR at f5 and BIS (R2=0.67, 0.79, and 0.71, in the adult_SEV, adult_DES, and ped_SEV groups, respectively). As an additional observation, a part of EMG activity at the gamma range of 30-47 Hz probably influenced the calculations of BIS and PPAR_f5 with a non-negligible level. The logarithm of PPAR in the gamma band was most sensitive to state changes during the emergence process and could provide a new non-proprietary parameter that correlates with changes in BIS during measurement of anesthesia depth.